Proceedings of the 2nd International Conference on Innovative Research Across Disciplines (ICIRAD 2017) 2017
DOI: 10.2991/icirad-17.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Pragmatics Learning Tools to Improve Critical Thinking Skills

Abstract: Abstract-The research development in the first stage was aimed at arranging prototype of Pragmatics learning tools oriented problem-based learning model which could improve understading concept and students' ability to think logically and critically. The subject of this study were both Ganesha University of Education, Undiksha lecturers and the students of Indonesian Language and Literature Study Program in the 4 th semester. The research method used was descriptive qualitative method that compraised the fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This study was consistent with the studies of Pradita (2014) and Wisudariani and Sriasih (2017) which proved the positive effect of teaching pragmatic features and using questions on developing critical thinking skills. It was proved that the integration of pragmatic features developed reasoning ability and students' ability to find out the clues through the sentences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study was consistent with the studies of Pradita (2014) and Wisudariani and Sriasih (2017) which proved the positive effect of teaching pragmatic features and using questions on developing critical thinking skills. It was proved that the integration of pragmatic features developed reasoning ability and students' ability to find out the clues through the sentences.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the results agreed with Ishihara (2012) who stressed that using critical discussion through negotiating pragmatic meaning promoted critical interpretation. Also, Suryoputro and Suyatno, (2017) as well as Wisudariani and Sriasih (2017) indicated that using pragmatic materials had a central role in learners' critical thinking development. These materials helped learners discover and use their own analytical abilities through critical review and thus improved students' ability to think logically and critically.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The 21 st -century learning in the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era requires human resources with competence, and the student achievements are directed at learning skills and innovations, including critical thinking skills (CTS) (Mafarja et al, 2022;Wisudariani & Sriasih, 2017), problem-solving skills, creativity (Sandopa & Doyan, 2022), and innovation (Ahmed & Asiksoy, 2021). The speed of technology and information not only affects our lifestyle or the development of education out there, but also affects how to educate students (Troise et al, 2022).…”
Section: Introductionmentioning
confidence: 99%